IMPLEMENTASI KEBIJAKAN PEMERINTAH KOTA PEKANBARU DALAM PENGENDALIAN DAN PENANGGULANGAN RABIES TAHUN 2013 - Mega Gustin; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The background about the implementation of mayor’s policies regulation is less than optimal the implementation of mayor’s regulation numbers 23 of 2012 about control and prevention of rabies in Pekanbaru can be seen there are still many populations of rabies animal’s spreader and also gite case that seleneed positive to rabies. Many people doesn’t know and don’t care and about mayor’s regulation number’s 23 of 2012. The purpose of this research is to know about mecanism of mayor’s regulation implementation process, number 23 of 2012 and whater abstracles that happen in that implementation of regulation to so make the implementation isn’t optimal. This Theory concept that used propound the factors that influencing policy implementatoin of Edward III collaboration, that is comunication resource and disposision. The method used in this research is discriptive, with qualitative approach. Data collection technique taht used were interview, observation, and documentation.the data type used was primary data obtained from the field and secondary data obtained where research is ussualy not available bsed on research result through interview and documentation. It can be seen that implementation of mayor’s regulation number 23 of 2012 about control and prevention of rabies is still not optimal. There are still have shortages in implementation of mayor’s regulation. The factors that influence this mayor’s regulation number 23 of 2012 is comunication, disposition, resource, and bureacracy system factors. Key words: implementation policy key, control, prevention